Management of the axilla following neoadjuvant chemotherapy for breast cancer- A change in practice. Issue 1 (February 2021) - Riogi, Bahaty; Sripadam, Raj; Barker, David; Harris, Olga; Innes, Helen; Chagla, Leena
Abstract: Objectives: Chemotherapy in the neo adjuvant setting has allowed downsizing of breast tumours thus allowing patients to benefit from breast conservation surgery. The effect of neoadjuvant chemotherapy (NAC) has also been observed in the axilla but most units are still treating the axilla with axillary lymph node dissection (ALND). Materials and methods: A prospective database of breast cancer patients receiving NAC between 2007 and 2016 at a single breast unit was reviewed. The management of the axilla and outcomes was studied. Results: 165 patients received NAC, 123 (74.5%) were clinically/radiologically node positive and 42 were negative. Median age was 50 years. 26.7% had triple negative disease and 34.5% were HER2 positive. 56/123 (45.5%) patients with positive nodes at the outset responded completely to NAC. 40 patients with positive nodes pre-NAC had post NAC SLNB with 37 requiring adjuvant radiotherapy only. 83/123 went directly to ALND post NAC and of these 27 were node negative and therefore may be considered to have had an unnecessary ALND. Overall mortality was 20.6% (34), local recurrence in the breast or mastectomy scar was 3.6% (6) but there was no recurrence in the axilla (0/165) with a median follow up of 67 months. Conclusion: There is no clear evidence for management of the axilla post NAC. We have used best available evidence to change our practice over the years and our results should encourage others to de-escalate treatment of the axilla in line with the recently published multidisciplinary guidance on axillary surgery following neoadjuvant chemotherapy. Highlights: 45.5% of axillary disease prior to neoadjuvant chemotherapy completely responded 1/3 of initial pathological nodes had SLNB & adjuvant radiotherapy to nodal basin There has been no reported axillary recurrence after median follow up of 67 months. SLNB alone can be considered after good axillary response to neoadjuvant chemotherapy.